Financial Performance, Dividend Payment and Firm Value An Exploratory Research on Vietnam Listed Firms in the Food and Drink Industry - Giang, Ngo Thu; Tuan, Dang Anh (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2016)
Abstract This research studies the relationships between dividend payment and the market value of listed firms in the food and drink industry in the period 2010 to 2014 inVietnam. The research finds empirically applicable factors in corporate finance and the management of stock listings in the stock exchange. The research develops an exploratory model reflecting the market value of the firms in the food and drink industry in the Vietnamese stock market in relation to their financial performance and dividend payments. The research also finds that in the food and drink industry inVietnam, firms will be more attractive in the stock exchange if they pay dividends in cash, achieve high gross margins, and mobilize a low debt ratio at a low mobilization cost. Received 16 February 2016, revised 9 June 2016, accepted 28 June 2016 Keywords: Financial performance, dividend payment, market value, listed firm, beverage and food industry, Vietnamese stock exchange.